Time-Invariant Superfluid Quantum Space as the Unified Field Theory - Amrit S. Šorli; Štefan Čelan (Reports in Advances of Physical Sciences, 2020)
The novelty of 21st-century physics is the development of the “superfluid quantum vacuum” model, also named “superfluid quantum space” that is replacing space-time as the fundamental arena of the universe. It also represents the model that has the potential of unifying four fundamental forces of the universe. Superfluid quantum space is represented as the time-invariant fundamental field of the universe where time is merely the duration of material changes.